INSIGHTS FROM A TEN-YEAR RETROSPECTIVE STUDY ON CHORANGIOMAS - Kochoska, Milka; Krsteska, Blagica; Bajdevska-Dukoska, Daniela; Risteski, Vladimir; Ristovski, Gligor; Milkovski, Daniel; Kostadinova-Kunovska, Slavica; Petrushevska, Gordana (Journal of Morphological Sciences, 2025)
The most common benign neoplasms of the placenta are non-trophoblastic tumors. The most common subtype is chorioangioma, but teratoma, leiomyoma, and hepatocellular adenoma are also seen. Giant chorioangioma is a rare tumor, with diameter larger than 4 cm and seen in association with elderly primipara, twin pregnancies, hypertension and diabetes. Giant chorioangioma is associated with complications that can affect both the mother and the fetus or neonate. We present a retrospective study of chorangioma cases diagnosed at Institute of Pathology in Skopje in a 10-year period from 2012 to 2021. Macroscopic observations, gestational age at delivery, maternal age, and pregnancy outcomes were assessed. Histological and immunohistochemical examinations of the placental chorangiomas were conducted. Six cases of chorangiomas were clinically identified and histopathologically confirmed. Four cases involved giant chorangiomas ranging in size from 8 to 13 cm. One case was identified as chorangioma of the umbilical cord. Three of the cases showed potential maternal risk factors like primary infertility, extreme obesity and post COVID status. Four of the pregnancies had favorable outcomes with no complications during and after birth, one of the pregnancies resulted in a premature birth, while the other was complicated by fetal distress. Regular monitoring by serial ultrasound and fetal echocardiography is recommended to pick up complications early so that they can be dealt effectively.